COMMUNITY FOREST MANAGEMENT (CFM) IN HOA BINH PROVINCE: STATUS AND SOLUTIONS - Thanh Que, Pham; Phuong Nam, Pham; Nghia Bien, Nguyen (Journal of Forestry Science and Technology, 2018)
Community forest management in Hoa Binh province has been established in association with the traditions, beliefs and culture of the communities. Hoa Binh province has allocated 48,771.19 ha of forestland to the ieshandreds of ethnic communities, accounting for 14.04% of the total forestland of the province; This policy has contributed to improving the income, especially of the poor, creating works for local people and enhacing the awareness of local communities on the role and the multi-values of forestland. However, the community forest management in Hoa Binh province have encountered many difficulties. Therefore, to improve the effectiveness of community forest management, it is necessary to promote allocation of forestland and issuance forestland use rights to local commmitities, to attract more human resources from the community in the management, to diversify the types of payment for forest environment fees and to improve forest values.